Meta‐Separation: Complete Separation of Organic–Water Mixtures by Structural Property of Metamaterial. Issue 11 (3rd May 2021) - Choi, Kyoung Hwan; Hwang, Da Young; Park, Jeong Eon; Suh, Dong Hack
Abstract: The separation of liquid mixtures has been studied for a long time. Separation is based on the difference in physical properties including pore size and electrostatic interaction. Therefore, there are many difficulties in separation of materials having similar physical properties such as ethanol–water and 1, 4‐dioxane–water mixtures. While pervaporation based on a difference in transport rates by permeability through a membrane has been suggested, it still has many difficulties such as high energy consumption and huge facilities. Yet there is an existing technical gap to remove trace amounts of organics dissolved in water. Here, a novel separation strategy employing a metamaterial, called meta‐separation using the exotic structural property of metamaterials rather than electrostatic characteristics is reported. The structural properties of metamaterials provide various functions of super‐hydrophobicity based on roughness of surface, the strong capillary effect based on nanopore, and huge void for great absorption of organics. It exhibits a water contact angle of 151.3° and high adhesive property from nanopore. On the other hand, ethanol is immediately absorbed up to 93 wt%. These differences make it possible to quickly and easily eliminate organics dissolved in water. Furthermore, their applications are expected to achieve functions in environmental remediation, biofuel separation process, etc., without large‐scale facilities. Abstract : Metal–organic framework with large surface area is used for gas separation and polymeric membrane is mainly studied in liquid separation. Contrary to these, the structure forms a very small surface area and a large volume to remove pollutants in water. A valance between superhydrophobic surface and nanocapillary force of huge void makes elimination of pollutant without energy consumption.